Lehmann, J. y Scheding, P. (eds.) (2023) Explaining the Urban Boom. A comparison of regional city development in the Roman provinces of North Africa and the Iberian Peninsula, Iberia Archaeologica 22. Madrid y Wiesbaden: Deutsches Archäologisches Institut y Harrassowitz Verlag, 330 páginas. ISBN 9783447121224, https://publications.dainst.org/books/dai/catalog/book/1244 - Funari, Pedro Paulo (SPAL - Revista de Prehistoria y Arqueología, 2024)
Review of the book: Explaining the Urban Boom. A comparison of regional city development in the Roman provinces of North Africa and the Iberian Peninsula, Iberia